2016
DOI: 10.1113/jp272927
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine released by endothelial cells facilitates flow‐mediated dilatation

Abstract: Key points The endothelium plays a pivotal role in the vascular response to chemical and mechanical stimuli.The endothelium is exquisitely sensitive to ACh, although the physiological significance of ACh‐induced activation of the endothelium is unknown.In the present study, we investigated the mechanisms of flow‐mediated endothelial calcium signalling.Our data establish that flow‐mediated endothelial calcium responses arise from the autocrine action of non‐neuronal ACh released by the endothelium. AbstractCirc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
124
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 103 publications
(142 citation statements)
references
References 156 publications
(335 reference statements)
6
124
0
1
Order By: Relevance
“…Endothelial cells are fixed in physical space and the physical connections between cells are invariant; the arrangement is a mesh. Despite this fixed anatomy, and mesh cell arrangement, the number of functional communication routes in the endothelium is large and gives rise to multiple possible outputs ([48], see Figure 4). Even a casual glance at communication across the endothelium shows the complex varying paths on activation (Video S2).…”
Section: Property 2: the Overall Behaviour Of The System Results Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial cells are fixed in physical space and the physical connections between cells are invariant; the arrangement is a mesh. Despite this fixed anatomy, and mesh cell arrangement, the number of functional communication routes in the endothelium is large and gives rise to multiple possible outputs ([48], see Figure 4). Even a casual glance at communication across the endothelium shows the complex varying paths on activation (Video S2).…”
Section: Property 2: the Overall Behaviour Of The System Results Frommentioning
confidence: 99%
“…In our own studies of endothelial Ca 2+ signalling, we observed Ca 2+ waves that seemingly propagate across clusters of cells in both pressurised and en face arteries. The propagation of Ca 2+ waves among groups of cells was most apparent during prolonged (∼5–10 min) activation with an agonist (GSK1016790A, 30 nM) of transient receptor potential cation channel subfamily V member 4 (TRPV4) (Figure 2 and Video S3 in the supplemental information online) [48]. The coordinated nature of these waves suggests that the endothelium has a modular architecture.…”
Section: Property 2: the Overall Behaviour Of The System Results Frommentioning
confidence: 99%
“…To block IP 3 Rs, we used both 2‐APB and caffeine. 2‐APB is a broad‐spectrum inhibitor that, although effective in blocking IP 3 Rs in native endothelial cells, may inhibit Ca 2+ entry pathways (see Peppiatt et al, ; Trebak, Bird, McKay, & Putney, ; Voets et al, ; Wilson, Lee, & McCarron, ). However, in the present experimental conditions, 2‐APB did not reduce the slow global Ca 2+ rise evoked by activation of TRPV4 channels suggesting that it is not inhibiting influx in the present experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial Ca 2+ signals were extracted automatically from fluorescence recordings using custom written Python software (; Lee et al, ; Wilson, Lee, & McCarron, ; Wilson, Saunter, et al, ). In brief, cellular regions of interest (ROIs) were first generated from average‐intensity projections of each time series recording.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation